PENGARUH INTERNET BANKING, KUALITAS LAYANAN, REPUTASI PRODUK, LOKASI, TERHADAP LOYALITAS NASABAH DENGAN INTERMEDIASI KEPUASAN NASABAH - ADINOTO NURSIANA (Jurnal Keuangan dan Perbankan, 2015)
Customer loyalty is one of the important factor that affect the growth of the bank.  This research examined  the effect of internet banking, service quality, reputation, product, and location  on customer loyalty with the intermediation  customer satisfaction. As analycal tool in this research is using software LISREL 8.80.Result from  this research. first, internet banking has a negative and not significant impact on customer satisfaction and customer layalty,  second, service quality, reputation, product, and location  have a positif and significant impact on customer satistaction, but its have a negative and not significant impact on customer layalty, third, customer satisfaction has a negative and not significant impact on customer loyalty.  So as to enhance customer loyalty, banks need to provide the best relationship between bank’s marketer and customer.